Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Motivasi pada UMKM di Wilayah Kabupaten Banjar - M. Haris Syafitri; Ayu Niken Faizati; Abdul Kadir; Noorlaily Maulida; Dewi Ariefahnoor; Lamsah Lamsah (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in both the national and local economies, including in Banjar Regency. However, MSMEs often face significant challenges in managing human resources (HR), which can directly affect employee motivation levels. This community service activity aims to provide education and support to MSME actors in Banjar Regency regarding effective HR practices, with a focus on improving work motivation. The methods used include socialization, training, and guidance in implementing a simple yet effective motivation system. The results of the activity showed an increase in participants' understanding and application of better HR strategies. It is hoped that this will have a positive impact on the productivity and sustainability of MSMEs in Banjar Regency, as well as contribute more to the local economy. The guidance provided also helps MSME actors better understand the importance of motivation in creating a productive work environment, which in turn can increase the competitiveness of their businesses in an increasingly competitive market.